Management accounting systems in Islamic and conventional financial institutions in Malaysia - Abdul Rasid, Siti Zaleha; Abdul Rahman, Abdul Rahim; Wan Ismail, Wan Khairuzzaman (Emerald Group Publishing Limited, 2011)
The purpose of this paper is to explore whether there is any difference in the management accounting systems (MAS) of conventional and Islamic Financial Institutions (IFIs) in Malaysia.